Reorientasi Fiqh Siyasah dalam Kontestasi Politik Digital: Analisis Etika Kampanye di Media Sosial Perspektif Maqashid al-Syariah - Asep Sobirin (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2025)
This research aims to analyze the dynamics of identity politics in Indonesia's digital era from the perspective of legal politics and Maqasid al-Shari’ah. The study focuses on how primordial identities are mobilized through social media and its impact on national resilience. Using a qualitative method with a juridical-normative approach, this research compares Western, customary, and Islamic legal systems while integrating classical and modern Islamic political thoughts. The findings reveal that current election regulations in Indonesia, particularly Law No. 7 of 2017, possess legal loopholes regarding digital campaigns, leading to judicial uncertainty. Furthermore, the analysis through Ibn Khaldun’s theory of ‘ashabiyyah shows that digital solidarity often shifts towards destructive polarization rather than constructive social cohesion. This manuscript also incorporates Al-Mawardi’s concept of leadership criteria and Yusuf al-Qaradawi’s framework on modern statehood to offer an ethical-legal solution. The value of this research lies in its multidisciplinary synthesis, proposing a transformation from symbolic identity politics to objective-idealistic politics as envisioned by Kuntowijoyo. By aligning constitutional principles with the essence of Shari’ah, this study provides a strategic framework for strengthening election regulations and digital ethics to safeguard the integrity of Indonesian democracy. It concludes that legal discovery by judges and ethical education for digital volunteers are crucial to mitigating the negative excesses of identity politicization in the upcoming electoral cycles.